Spontaneous extrusion of staghorn renal calculus with nephrocutaneous fistula in a child - Purkait, Bimalesh (BMJ Case Rep, 2016)
Renal stone disease may present as nephrocutaneous fistula. Spontaneous extrusion of renal stone with nephrocutaneous fistula is rare. Most of the cases have been reported in adults. We present a case of nephrocutaneous fistula with spontaneous extrusion of staghorn renal calculus in a paediatric patient.